2023
DOI: 10.1007/s00204-023-03614-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphenol A on the neurological system: a review update

Henrique Eloi Costa,
Elisa Cairrao

Abstract: Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC) and one of the most produced synthetic compounds worldwide. BPA can be found in epoxy resins and polycarbonate plastics, which are frequently used in food storage and baby bottles. However, BPA can bind mainly to estrogen receptors, interfering with various neurologic functions, its use is a topic of significant concern. Nonetheless, the neurotoxicity of BPA has not been fully understood despite numerous investigations on its disruptive effects. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 213 publications
0
2
0
Order By: Relevance
“…Several mechanisms have been proposed to explain the potential negative impact of BPA on cognitive functions [52,53]. Both in vivo and in vitro studies have demonstrated the effect of BPA on apoptosis, oxidative stress, inflammation, mitochondrial dysfunction, and endoplasmic reticulum stress [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the potential negative impact of BPA on cognitive functions [52,53]. Both in vivo and in vitro studies have demonstrated the effect of BPA on apoptosis, oxidative stress, inflammation, mitochondrial dysfunction, and endoplasmic reticulum stress [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their impact on vascular health, endocrine disruptors have also been implicated in the pathogenesis of degenerative diseases. Epidemiological and experimental studies have revealed associations between exposure to these compounds and the development of Alzheimer's, Parkinson's, and certain types of cancer [90][91][92][93]. Disruption of hormone signaling pathways and insulin resistance, endothelial dysfunction, oxidative stress, chronic inflammation, alterations in lipid metabolism, and mitochondrial dysfunction are among the proposed mechanisms by which endocrine disruptors contribute to degenerative conditions [94][95][96].…”
Section: Environment and Endocrine Disruptorsmentioning
confidence: 99%
“…BPA interacts with several biological receptors such as estrogen receptor (ER), androgen receptor (AR), and thyroid hormone receptor (THR), resulting in endocrine-disrupting effects. These effects lead to adverse outcomes such as reproductive and developmental issues in the offspring, reproductive dysfunction, neurotoxicity, mutagenesis, and even cancer development [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%